Realitas Perkawinan Beda Agama pada Masyarakat Sangalla Selatan Kabupaten Tana Toraja (Analisis Hukum Islam) - Buhari Pamilangan; Anita Marwing (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2023)
This article discusses interfaith marriage in South Sangalla Subdistrict, Tana Toraja Regency with the following problems: 1) factors causing of interfaith marriage in South Sangalla Subdistrict, Tana Toraja Regency; 2) the implications caused by interfaith marriage in South Sangalla Subdistrict, Tana Toraja Regency; and 3) how to minimize interfaith marriage in South Sangalla Subdistrict, Tana Toraja Regency. This research is a qualitative study that uses normative theological, juridical, cultural sociological, and historical approaches. Data collection techniques were carried out through observation, interviews, and documentation. Interviews were conducted with religious leaders, community leaders, traditional leaders, the head of the religious affairs office (KUA), and perpetrators of interfaith marriages in South Sangalla District, Tana Toraja Regency. The results showed that: 1) the occurrence of interfaith marriages in South Sangalla Subdistrict, Tana Toraja Regency is due to several factors, namely: women's freedom to choose prospective husbands, legitimization of interfaith marriages by custom, lack of religious knowledge and feelings of like and love; 2) the implications of interfaith marriages, namely: it is difficult to realize the purpose of marriage because of differences in spiritual principles, so that it has the potential to cause disputes and cause problems for children, especially in determining the child's religion and school; and 3) efforts to minimize the occurrence of interfaith marriage can be done internally and externally.